Case report: Resolution of VIPoma-related symptoms with peptide receptor radionuclide therapy - Turgut Bora Cengiz; Raksha Kulkarni; Virginia Corbett; Nasrin V. Ghesani; Edward Wolin; Munir V. Ghesani (Frontiers in Oncology)
Peptide receptor radionuclide therapy (PRRT) is used for the management of neuroendocrine tumors (NETs) not responsive to somatostatin analogs. In this case series, we report two patients with pancreatic vasoactive intestinal peptide (VIP)-secreting NETs (VIPomas) not responsive to any other therapies who achieved symptomatic control and a significant decrease in serum VIP levels with PRRT during their hospital stay. Two patients with VIPomas were admitted to the hospital with multiple prior hospital admissions after going through multiple lines of therapy. The first patient was a 47-year-old woman with a grade 2 pancreatic VIP-secreting NET. She was treated with somatostatin analogs and chemotherapy; however, she experienced recurrent symptoms and complications leading to two hospital admissions, one of which included an intensive care unit (ICU) admission. The patient was treated with lutetium-177 DOTATATE while in the hospital, which led to the resolution of the symptoms and a marked decline in serum VIP levels, and she was able to be discharged from the hospital after 147 days of hospitalization (16 days after PRRT). The second patient was a 27-year-old man who was diagnosed with a well-differentiated grade 3 pancreatic VIPoma. He also suffered from severe diarrhea and was not responsive to any form of therapy, including liver embolization. He was also treated with PRRT on admission, which led to immediate resolution of his symptoms and a decrease in tumor markers. In conclusion, 177Lu-DOTATATE is an effective treatment for highly symptomatic VIPoma. Inpatient administration of PRRT can rapidly reduce diarrhea and fluid and electrolyte complications of VIP secretion and may shorten hospital stays.